Mechanisms by which the orexigen NPY regulates anorexigenic -MSH and TRH - Cyr, Nicole E (2013)
Protein posttranslational processing is a cellular mechanism fundamental to the generation of bioactive peptides, including the anorectic α-melanocyte-stimulating hormone (α-MSH) and thyrotropin-releasing hormone (TRH) peptides produced in the hypothalamic arcuate (ARC) and paraventricular (PVN) nuclei, respectively. Neuropeptide Y (NPY) promotes positive energy balance in part by suppressing α-MSH and TRH. The mechanism by which NPY regulates α-MSH output, however, is not well understood. Our results reveal that NPY inhibited the posttranslational processing of α-MSH's inactive precursor proopiomelanocortin (POMC) by decreasing the prohormone convertase-2 (PC2). We also found that early growth response protein-1 (Egr-1) and NPY-Y1 receptors mediated the NPY-induced decrease in PC2. NPY given intra-PVN also decreased PC2 in PVN samples, suggesting a reduction in PC2-mediated pro-TRH processing. In addition, NPY attenuated the α-MSH-induced increase in TRH production by two mechanisms. First, NPY decreased α-MSH-induced CREB phosphorylation, which normally enhances TRH transcription. Second, NPY decreased the amount of α-MSH in the PVN. Collectively, these results underscore the significance of the interaction between NPY and α-MSH in the central regulation of energy balance and indicate that posttranslational processing is a mechanism that plays a specific role in this interaction.